2014
DOI: 10.1371/journal.pone.0112219
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Transfer Prepared Gradient Echo MRI for CEST Imaging

Abstract: Chemical exchange saturation transfer (CEST) is an emerging MRI contrast mechanism that is capable of noninvasively imaging dilute CEST agents and local properties such as pH and temperature, augmenting the routine MRI methods. However, the routine CEST MRI includes a long RF saturation pulse followed by fast image readout, which is associated with high specific absorption rate and limited spatial resolution. In addition, echo planar imaging (EPI)-based fast image readout is prone to image distortion, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…Thus, here, an MT‐prepared GRE MRI sequence was used at 3 T. Results showed that, even though each MT pulse only generates a small increase in the CEST effect, it could accumulate short T R values over numerous saturation steps. The conclusions drawn here were consistent with those drawn by Dixon and colleagues . In addition, images based on GRE readout at short echo time showed little distortion of the image, rendering it more suitable for applications at 3 T and higher field strengths.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, here, an MT‐prepared GRE MRI sequence was used at 3 T. Results showed that, even though each MT pulse only generates a small increase in the CEST effect, it could accumulate short T R values over numerous saturation steps. The conclusions drawn here were consistent with those drawn by Dixon and colleagues . In addition, images based on GRE readout at short echo time showed little distortion of the image, rendering it more suitable for applications at 3 T and higher field strengths.…”
Section: Discussionsupporting
confidence: 91%
“…This improvement is comparable to previously published results (14,35). The previously observed effect of excitation flip-angle on CEST contrasts (34) was not clearly observed in our preliminary study (see Supporting Figs. S1 and S2).…”
Section: Discussionsupporting
confidence: 92%
“…This improvement is comparable to previously published results . The previously observed effect of excitation flip‐angle on CEST contrasts was not clearly observed in our preliminary study (see http://onlinelibrary.wiley.com/store/10.1002/mrm.26624/asset/supinfo/mrm26624-sup-0001-suppinfo.docx?v=1&s=0deb58a8a75b6624b7c7659677c08d9ee2c2269a). Nonetheless, homogeneous excitations were used in our imaging experiments to ensure that the comparison between the two saturation pulses was free from any potential influence caused by an inhomogeneous excitation pattern.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations